The Association of Thyrotropin and Autoimmune Thyroid Disease in Developing Papillary Thyroid Cancer - I-Shuan Lee; An-Tsz Hsieh; Ting-Wei Lee; Ting-I Lee; Yu-Mei Chien (International Journal of Endocrinology)
Background. Papillary thyroid carcinoma (PTC) is the most common type of malignant thyroid neoplasm. However, the incidence of PTC with autoimmune thyroid disease (AITD) varies between studies. This study aims to investigate whether patients with AITD have increased incidence of PTC. We also analyzed the relationship of serum thyroid-stimulating hormone (TSH) levels and PTC in relation to AITD based on histopathological data. Methods. A total of 533 participants who underwent thyroidectomy were enrolled in this retrospective study based on clinicohistopathological data and known thyroid autoantibodies. Patients were divided into PTC and benign groups according to histopathologic diagnosis. Age, gender, body mass index, and serum TSH level before thyroidectomy were recorded. Results. Of the 533 enrolled patients, 159 (29.8%) were diagnosed with PTC, of which 38 (35.5%) had Hashimoto’s thyroiditis (HT). More patients with HT were female, and patients with HT, Graves’ disease, and thyroid nodules with higher TSH level had a higher incidence of PTC. Conclusions. A high proportion of the patients with PTC had HT. There was a trend that a higher serum TSH level was associated with a greater risk of thyroid cancer.